Vorinostat: a histone deacetylases (HDAC) inhibitor ameliorates traumatic brain injury by inducing iNOS/Nrf2/ARE pathway - Xu, Jinyu; Shi, Jun; Zhang, Jiaming; Zhang, Yun (Folia Neuropathologica, 2018)
The present investigation evaluates the protective effect of vorinostat on neuronal cells in the traumatic brain injury (TBI) and also postulates the possible mechanism of its action. Marmarou’s weight-drop model was used to induce the TBI. Further, animals were treated with vorinostat 100 mg/kg intraperitoneally 30 min before the TBI induction. Neurological score and brain water content were determined in all the groups and thereafter oxidative stress parameters and adenosine triphosphate (ATP) content were determined in the neuronal tissues of TBI mice. Western blot assay and reverse transcription polymerase chain reaction (RT-PCR) was performed for the determination of the expression of several proteins in the neuronal tissues. Moreover, immunohistochemical staining and terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) assay was also done on the neuronal tissues of TBI mice. Data of the study reveal that treatment with vorinostat significantly reduces the altered level of grip test scores and water content in the brain of traumatic injured mice. Moreover, the altered level of oxidative stress parameters, translocation of nuclear factor erythroid 2-related factor 2 (Nrf2) and ATP content was attenuated by treating TBI mice with vorinostat. Also treatment with vorinostat ameliorates the altered expression of p-Akt, NF-B, iNOS and caspase by the western blot assay in the neuronal tissue of TBI mice and mRNA level of HO-1 and NQO-1 significantly enhanced in vorinostat compared to the negative control group. Furthermore, the TUNEL assay also reveals that the apoptosis of neuronal cells was significantly (p < 0.01) reduced in the vorinostat-treated group compared to the negative control group. The present study concludes that vorinostat protects the neuronal injury in TBI mice by reducing the altered level of oxidative stress and inflammatory response.